Systematic Analysis of The Implementation of Problem Based Learning (PBL) and Project Based Learning (PjBL) Models in Science and Mathematics Education in Indonesia - Ruruh Rachmawati; Bonita Ariestiani; Ayu Syafitri; Nurasiah Nurasiah; Syamsiah Syamsiah; Dewi Setyawati; Kiki Sukirman; Andri Suryana (Pascasarjana, Mataram University, 2026)
This systematic literature review analyzes the implementation of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models in Science and Mathematics education within Indonesia. Using the Systematic Literature Review (SLR) method guided by PRISMA guidelines, this study examined 21 articles from Sinta-accredited journals (2020-2025). The findings indicate that the PBL model is highly effective in enhancing students' critical thinking skills, problem-solving abilities, and cognitive learning outcomes. Conversely, the PjBL model demonstrates a more significant impact on fostering creativity, collaboration, and 21st-century skills. A synthesis of the results reveals that both models support active and contextual learning, aligning with the principles of Indonesia's Merdeka Curriculum and the Pancasila Student Profile. This study concludes that PBL and PjBL offer distinct yet complementary benefits. For optimal implementation, teacher training and contextual adaptation are crucial. The integration of these models presents a strategic approach to advancing Science and Mathematics education by developing a generation that is intellectually competent, innovative, and collaborative